A systematic review of adeno-associated virus gene therapies in neurology: the need for consistent safety monitoring of a promising treatment. Issue 12 (8th September 2022) - Horton, Rebecca H; Saade, Dimah; Markati, Theodora; Harriss, Elinor; Bönnemann, Carsten G; Muntoni, Francesco; Servais, Laurent
Abstract : Adeno-associated virus (AAV) gene therapies are generating much excitement in the rare disease field, particularly for previously untreatable neurological conditions. Efficacy has been claimed for several gene therapy products and the number of trials is rapidly increasing. However, reports of severe treatment-related adverse reactions are emerging, including death. There is still insufficient knowledge about their aetiology, prevention and treatment. We therefore undertook to systematically review publicly available data on AAV gene therapies in order to collate existing information on both safety and efficacy. Here, we review emerging efficacy reports of these novel therapies, many of which show promise. We also collate an increasing number of adverse reactions. Overwhelmingly, these results make a case for unified reporting of adverse events. This is likely to be critical for improving the safety of these promising treatments.